Penyelesaian Sengketa Terhadap Pemegang Hak Merek Dagang Yang Digunakan Pihak Lain Sebagai Nama Domain - AR, Azhari; Rahmadani, Gema; AR, Zulkifli; Faisal, Muhammad; Daud Syah, Teuku (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
Losses to brand rights that other parties use as a domain name to gain profit from the fame of a brand, resulting in the term brand piracy through a domain name. Cybersquatting is an act of brand piracy through domain names, parties who hijack or create domain names by imitating famous brand names and then resell them to other parties. For companies that already have a good reputation and are known in the wider community, this is certainly very disturbing, because this is related to the company's big name and good name. Settlement of trademark rights used by other parties as domain names is resolved through litigation through a court institution. Litigation dispute resolution is regulated in Law Number 15 of 2001 concerning Trademarks from Article 76 to Article 83, while nonlitigation dispute resolution is dispute resolution outside of court, such as through alternative dispute resolution or arbitration. Keywords: Legal Protection, Brands, Domain Names.